MAIN STAGES OF THE HISTORY OF DEVELOPMENT OF FAMILY MEDICINE IN UKRAINE AND THE UKRAINIAN ASSOCIATION OF FAMILY MEDICINE - Matjukha, L.; Babinets, L.; Khimion, L.; Nadutyj, K.; Kolesnyk, P.; Bazylevych, A.Ja.; Zaremba, E. (Українські медичні вісті, 2023)
The article presents in the historical aspect the development of general practice — family medicine, presents the founders of this specialty, its educational, organizational, clinical aspects, international cooperation. The activity of the Ukrainian Association of Family Medicine, which is a platform for uniting primary care doctors and teachers of the departments of family medicine to develop joint proposals for the development of primary health care based on the principles of family medicine in Ukraine, improving the quality of education and work of a family doctor, is highlighted.